Oropharyngeal cancer associated with human papillomavirus. A Case Report - Lianet Pérez Rodríguez; Grisel Utrera Díaz; Miriam Magaly González González del Pino; Leydis Macías Ortiz (Medisur)
Oral and oropharyngeal cancer is the seventh most common cause of cancer-related mortality. Relation between human papillomavirus infection and head and neck cancer has been showed. A case of 68-year-old white male patient of rural origin with a history of apparent good health is presented. He was an inveterate smoker with irregular sexual activity who presented to consultation two years ago, after suffering from dysphonia for 3 months. The case was consulted with the specialty of otolaryngology and acute pharyngitis was diagnosed. Three months later, he continued affected by a more severe dysphonia. Severe epithelial dysplasia associated with human papillomavirus was observed through a direct laryngoscopy. Two-year treatment with recombinant alfa-2b Interferon was prescribed. The patient progressed for 2 years, subsequently presenting constant dysphonia, symptoms of rhinorrhea and flu-like symptoms. Well-differentiated invasive squamous cell carcinoma was diagnosed and a laryngectomy was performed. This case is presented because of the importance of knowing the etiology of these lesions attributed to the human papillomavirus for increasing people’s awareness of the risk factors and thus, reduce its prevalence.